Peran Badan Usaha Milik Desa (BUMDES) dalam Pengelolaan Obyek Wisata Di Desa Ekasari Kabupaten Jembrana - I Gusti Putu Ghosadhira Vedhastama; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Village-Owned Enterprises are institutions that were formed as an effort by the village government to improve the welfare of rural communities in accordance with their potential. Ekasari Village, which is located in Jembrana Regency, has established BUMDes since 2006. Ekasari Village has tourism potential and really needs the role of BUMDes for its management. This study examines two things: the implementation of tourism object management by the Village-Owned Enterprises in Ekasari Village and the efforts to manage Maria Palasari Caves to increase Village Original Income. The purpose of this study was to analyze the management of tourism objects by the Ekasari Village Owned Enterprise. This study was conducted using empirical methods and a sociological approach to law. There are two sources of legal materials for this study, namely: primary legal materials and secondary legal materials. Data collection techniques, through interview techniques and literature study. The results showed that the Ekasari BUMDes made efforts related to the implementation of tourism object management, namely by coordinating with the tourism object managers so that they could be managed directly by the Ekasari BUMDes. In addition, the role of the Village Government, Ekasari BUMDes to the community is very necessary in order to achieve the prosperity of the Village community through the management of tourism objects that are structured by the Ekasari BUMDes.